Internal and external governance in UK companies - O'Sullivan, Cornelius Noel (2000)
The 1990s witnessed an increased interest in issues of governance and accountability in U.K. companies. In the wake of a series of governance reports (e.g. Cadbury, 1992; Greenbury, 1995; Hampel, 1998), U.K. companies have significantly altered their governance characteristics. The objective of this thesis is to examine the utilisation of governance mechanisms by U.K. companies immediately prior to the beginning of this governance revolution. My first objective is to ascertain the extent to which board composition and leadership, managerial ownership and external shareholder control were substitutes or complements in the overall governance strategies employed by large quoted companies at the beginning of the 1990s. My second objective is to examine the relationship between internal and external governance mechanisms. This is accomplished in two ways. First, I investigate the internal governance characteristics of takeover targets and a matched sample of non-targets to ascertain the influence of internal governance characteristics at various stages of the takeover process. The motivation for this investigation is a perception in the governance literature that takeovers represent a governance mechanism of last resort exercised only when internal governance structures are ineffective in aligning the interests of managers and shareholders. Second, I examine the governance characteristics of mutual and proprietary insurance companies. In mutual insurance companies, the functions of owner and policyholder are merged which eliminates the prospect of governance either through takeovers or through the ownership of substantial proportion of equity. The absence of these two governance mechanisms suggests that mutual insurers may place greater reliance on internal governance such as more intensive monitoring by the board of directors. In the case of large quoted companies, I find a significant substitution between the monitoring potential of both external and internal ownership and the utilisation of non-executive directors. I also find that companies with greater nonexecutive representation on their boards are more likely to acquire the complementary monitoring of directors' and officers' insurance and demand more extensive auditing. Managerial ownership is the dominant influence on the takeover process. Hostile and unsuccessful bids are associated with lower levels of managerial ownership while friendly and successful bids are associated with high ownership levels. I also find some evidence that hostile targets possess less independent boards compared to a matched sample of non-targets. In the case of insurance companies, I find that mutuals place greater emphasis on non-executive directors than their proprietary counterparts. Overall, my empirical analysis suggests that, at the beginning of the 1990s, U.K. companies emphasised different governance mechanisms depending on the specific monitoring problems they faced.